Hubungan Karakteristik Petani dengan Tingkat Adopsi Inovasi OPIP Padi 400 di Kecamatan Bendosari Kabupaten Sukoharjo - Yulia Hernan Puspita; Sugihardjo Sugihardjo; Suwarto Suwarto (AGRITEXTS: Journal of Agricultural Extension, 2024)
The implementation of the Optimization of Rice Land Index Improvement 400 (commonly called OPIP Padi 400) in Bendosari Sub-district has yet to be fully realized. Some of farmers still unsure, are in the process of implementing, or have not and not implemented the program. This is because the rate of innovation adoption is influenced by the characteristics of the adoptees. This study aimed to determine factors forming characteristic of farmers, farmer adoption rate in the program, examines relationships between farmer characteristics with their adoption Rate, the difference in OPIP Padi 400 adoption rate between farmers on paddy fields and dry land. Quantitative research design was used. In this research Mulur, Mojorejo, Cabeyan, and Puhgogor Villages of Bendosari Sub-district were purposively selected. Disproportionate random sampling was used to sample 68 farmers. Quantitative data were analyzed using rank spearman and Mann Whitney with IBM SPSS Statistics 25 program. The results showed that there was a significant relationship between farmer characteristics with adoption rate of OPIP Padi 400 innovations, such as age, non-formal education, land ownership, farmer group membership, and farming experience. Formal education, number of household members, and farmland size are not significantly related. A comparison of the adoption rate of OPIP Padi 400 between farmers in paddy fields and dry land obtained Asymp.Sig (2-tailed) of 0.058, which means that there is no significant difference at the 95% confidence level (α = 0.05).